Producing open source software : How to run a successful free software project - Fogel, Karl (California O'reilly Media, 2006)
Producing Open Source Software is a book about the human side of open source development. It describes how successful projects operate, the expectations of users and developers, and the culture of free software.
Includes index
Keywords: Công nghệ thông tin